Four Plasma Glucose and Insulin Responses to a 75 g OGTT in Healthy Young Japanese Women - Kei Takahashi; Hidetaka Nakamura; Hiroshi Sato; Hideto Matsuda; Kazuo Takada; Tomiko Tsuji (Journal of Diabetes Research)
The incidence of diabetes has been gradually increasing, not only in middle-aged individuals but also in young individuals. However, insulin and glucose patterns have not been investigated in apparently healthy young individuals, as they are typically grouped as controls. In this study, we investigated and classified glucose and insulin patterns in healthy young women. Sixty-two nonobese women without metabolic disease were recruited. The subjects underwent a 75 g oral glucose tolerance test (OGTT), physical measurements, and a biochemical examination. Two subjects displayed impaired glucose tolerance. The 62 subjects were categorized into four patterns by plasma glucose and insulin peak time during OGTT: normal type (n=39), insulin-late type (n=11), insulin- and glucose-late type (n=7), and insulin-very late type (n=5). OGTT glucose and insulin levels at all time points, insulinogenic index, HOMA-IR, and glucose area under the curve (AUC) significantly differed among the four groups. However, insulin AUC did not significantly differ. We did not detect significant differences in body condition or biochemical measurements. Our study demonstrated that some healthy young individuals might have delayed insulin secretion by OGTT. Early detection of altered glucose metabolism might be helpful to improve lifestyle choices and prevent progression to diabetes.